Cooperativity between stromal cytokines drives the invasive migration of human breast cancer cells. (19th August 2019) - Elisha, Yair; Sagi, Yael; Klein, Georg; Straussman, Ravid; Geiger, Benjamin
Abstract : The cross-talk between cancer cells and the stromal microenvironment plays a key role in regulating cancer invasion. Here, we employed an ex vivo invasion model system for exploring the regulation of breast cancer cells infiltration into a variety of stromal fibroblast monolayers. Our results revealed considerable variability in the stromal induction of invasiveness, with some lines promoting and others blocking invasion. It was shown that conditioned medium (CM), derived from invasion-promoting fibroblasts, can induce epithelial–mesenchymal transition-like process in the cancer cells, and trigger their infiltration into a monolayer of invasion-blocking fibroblasts. To identify the specific invasion-promoting molecules, we analysed the cytokines in stimulatory CM, screened a library of purified cytokines for invasion-promoting activity and tested the effect of specific inhibitors of selected cytokine receptors on the CM-induced invasion. Taken together, these experiments indicated that the invasiveness of BT-474 is induced by the combined action of IL1 and IL6 and that IL1 can induce IL6 secretion by invasion-blocking fibroblasts, thereby triggering cancer cell invasion into the stroma. This unexpected observation suggests that stromal regulation of cancer invasion may involve not only cross-talk between stromal and cancer cells, but also cooperation between different stromal subpopulations. This article is part of a discussion meeting issue 'Forces in cancer: interdisciplinary approaches in tumour mechanobiology'.